Intensity calibration and sensitivity factors for XPS instruments with monochromatic Ag Lα and Al Kα sources. (26th April 2019) - Shard, Alexander G.; Counsell, Jonathan D.P.; Cant, David J. H.; Smith, Emily F.; Navabpour, Parnia; Zhang, Xiaoling; Blomfield, Christopher J.
Abstract : This paper provides a description of the transmission function of an X‐ray photoelectron spectroscopy (XPS) instrument operating with exchangeable Al Kα (1486.6 eV) and Ag Lα (2984.3 eV) sources. Both sources use the same quartz crystal monochromator and illuminate the same area of the sample. The transmission‐function–corrected data from sputter cleaned gold provides a useful reference material to calibrate other instruments of the same type. Sensitivity factors for Ag Lα and Al Kα are calculated from photoionisation cross sections and electron effective attenuation lengths. These compare well with previous experimental values and data acquired from ionic liquids. The intensity of the Ag Lα source is found to be approximately 50 times lower than the Al Kα source. This, coupled with generally lower photoemission efficiencies, results in noisier data or extended acquisition times. However, there are clear advantages to using the Ag Lα source to analyse certain elements where additional core levels can be accessed and for many technologically important elements where interference from Auger electron peaks can be eliminated. The combination of calibrated data from both sources provides direct and easily interpreted insight into the depth distribution of chemical species. This could be particularly important for topographic samples, where angle resolved experiments are not always helpful. We also demonstrate, using thin coatings of chromium and carbon, that the inelastic background in Ag Lα wide‐scan spectra has a significantly increased information depth compared with Al Kα.